/- Copyright (c) 2014 Jeremy Avigad. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: Jeremy Avigad, Leonardo de Moura Structures with multiplicative and additive components, including semirings, rings, and fields. The development is modeled after Isabelle's library. -/ import logic.eq logic.connectives data.unit data.sigma data.prod import algebra.binary algebra.group open eq eq.ops variable {A : Type} /- auxiliary classes -/ structure distrib [class] (A : Type) extends has_mul A, has_add A := (left_distrib : ∀a b c, mul a (add b c) = add (mul a b) (mul a c)) (right_distrib : ∀a b c, mul (add a b) c = add (mul a c) (mul b c)) theorem left_distrib [distrib A] (a b c : A) : a * (b + c) = a * b + a * c := !distrib.left_distrib theorem right_distrib [distrib A] (a b c : A) : (a + b) * c = a * c + b * c := !distrib.right_distrib structure mul_zero_class [class] (A : Type) extends has_mul A, has_zero A := (zero_mul : ∀a, mul zero a = zero) (mul_zero : ∀a, mul a zero = zero) theorem zero_mul [simp] [mul_zero_class A] (a : A) : 0 * a = 0 := !mul_zero_class.zero_mul theorem mul_zero [simp] [mul_zero_class A] (a : A) : a * 0 = 0 := !mul_zero_class.mul_zero structure zero_ne_one_class [class] (A : Type) extends has_zero A, has_one A := (zero_ne_one : zero ≠ one) theorem zero_ne_one [s: zero_ne_one_class A] : 0 ≠ (1:A) := @zero_ne_one_class.zero_ne_one A s /- semiring -/ structure semiring [class] (A : Type) extends add_comm_monoid A, monoid A, distrib A, mul_zero_class A section semiring variables [s : semiring A] (a b c : A) include s theorem one_add_one_eq_two : 1 + 1 = (2:A) := by unfold bit0 theorem ne_zero_of_mul_ne_zero_right {a b : A} (H : a * b ≠ 0) : a ≠ 0 := suppose a = 0, have a * b = 0, by rewrite [this, zero_mul], H this theorem ne_zero_of_mul_ne_zero_left {a b : A} (H : a * b ≠ 0) : b ≠ 0 := suppose b = 0, have a * b = 0, by rewrite [this, mul_zero], H this local attribute right_distrib [simp] theorem distrib_three_right (a b c d : A) : (a + b + c) * d = a * d + b * d + c * d := by simp end semiring /- comm semiring -/ structure comm_semiring [class] (A : Type) extends semiring A, comm_monoid A -- TODO: we could also define a cancelative comm_semiring, i.e. satisfying -- c ≠ 0 → c * a = c * b → a = b. section comm_semiring variables [s : comm_semiring A] (a b c : A) include s protected definition algebra.dvd (a b : A) : Prop := ∃c, b = a * c definition comm_semiring_has_dvd [instance] [priority algebra.prio] : has_dvd A := has_dvd.mk algebra.dvd theorem dvd.intro {a b c : A} (H : a * c = b) : a ∣ b := exists.intro _ H⁻¹ theorem dvd_of_mul_right_eq {a b c : A} (H : a * c = b) : a ∣ b := dvd.intro H theorem dvd.intro_left {a b c : A} (H : c * a = b) : a ∣ b := dvd.intro (by rewrite mul.comm at H; exact H) theorem dvd_of_mul_left_eq {a b c : A} (H : c * a = b) : a ∣ b := dvd.intro_left H theorem exists_eq_mul_right_of_dvd {a b : A} (H : a ∣ b) : ∃c, b = a * c := H theorem dvd.elim {P : Prop} {a b : A} (H₁ : a ∣ b) (H₂ : ∀c, b = a * c → P) : P := exists.elim H₁ H₂ theorem exists_eq_mul_left_of_dvd {a b : A} (H : a ∣ b) : ∃c, b = c * a := dvd.elim H (take c, assume H1 : b = a * c, exists.intro c (H1 ⬝ !mul.comm)) theorem dvd.elim_left {P : Prop} {a b : A} (H₁ : a ∣ b) (H₂ : ∀c, b = c * a → P) : P := exists.elim (exists_eq_mul_left_of_dvd H₁) (take c, assume H₃ : b = c * a, H₂ c H₃) theorem dvd.refl [simp] : a ∣ a := dvd.intro !mul_one theorem dvd.trans {a b c : A} (H₁ : a ∣ b) (H₂ : b ∣ c) : a ∣ c := dvd.elim H₁ (take d, assume H₃ : b = a * d, dvd.elim H₂ (take e, assume H₄ : c = b * e, dvd.intro (show a * (d * e) = c, by rewrite [-mul.assoc, -H₃, H₄]))) theorem eq_zero_of_zero_dvd {a : A} (H : 0 ∣ a) : a = 0 := dvd.elim H (take c, assume H' : a = 0 * c, H' ⬝ !zero_mul) theorem dvd_zero [simp] : a ∣ 0 := dvd.intro !mul_zero theorem one_dvd [simp] : 1 ∣ a := dvd.intro !one_mul theorem dvd_mul_right [simp] : a ∣ a * b := dvd.intro rfl theorem dvd_mul_left [simp] : a ∣ b * a := by simp theorem dvd_mul_of_dvd_left {a b : A} (H : a ∣ b) (c : A) : a ∣ b * c := dvd.elim H (take d, suppose b = a * d, dvd.intro (show a * (d * c) = b * c, by simp)) theorem dvd_mul_of_dvd_right {a b : A} (H : a ∣ b) (c : A) : a ∣ c * b := !mul.comm ▸ (dvd_mul_of_dvd_left H _) theorem mul_dvd_mul {a b c d : A} (dvd_ab : a ∣ b) (dvd_cd : c ∣ d) : a * c ∣ b * d := dvd.elim dvd_ab (take e, suppose b = a * e, dvd.elim dvd_cd (take f, suppose d = c * f, dvd.intro (show a * c * (e * f) = b * d, by simp))) theorem dvd_of_mul_right_dvd {a b c : A} (H : a * b ∣ c) : a ∣ c := dvd.elim H (take d, assume Habdc : c = a * b * d, dvd.intro (!mul.assoc⁻¹ ⬝ Habdc⁻¹)) theorem dvd_of_mul_left_dvd {a b c : A} (H : a * b ∣ c) : b ∣ c := dvd_of_mul_right_dvd (mul.comm a b ▸ H) theorem dvd_add {a b c : A} (Hab : a ∣ b) (Hac : a ∣ c) : a ∣ b + c := dvd.elim Hab (take d, suppose b = a * d, dvd.elim Hac (take e, suppose c = a * e, dvd.intro (show a * (d + e) = b + c, by rewrite [left_distrib]; substvars))) end comm_semiring /- ring -/ structure ring [class] (A : Type) extends add_comm_group A, monoid A, distrib A theorem ring.mul_zero [simp] [ring A] (a : A) : a * 0 = 0 := have a * 0 + 0 = a * 0 + a * 0, from calc a * 0 + 0 = a * (0 + 0) : by simp ... = a * 0 + a * 0 : by rewrite left_distrib, show a * 0 = 0, from (add.left_cancel this)⁻¹ theorem ring.zero_mul [simp] [ring A] (a : A) : 0 * a = 0 := have 0 * a + 0 = 0 * a + 0 * a, from calc 0 * a + 0 = (0 + 0) * a : by simp ... = 0 * a + 0 * a : by rewrite right_distrib, show 0 * a = 0, from (add.left_cancel this)⁻¹ definition ring.to_semiring [trans_instance] [s : ring A] : semiring A := ⦃ semiring, s, mul_zero := ring.mul_zero, zero_mul := ring.zero_mul ⦄ section variables [s : ring A] (a b c d e : A) include s theorem neg_mul_eq_neg_mul : -(a * b) = -a * b := neg_eq_of_add_eq_zero begin rewrite [-right_distrib, add.right_inv, zero_mul] end theorem neg_mul_eq_mul_neg : -(a * b) = a * -b := neg_eq_of_add_eq_zero begin rewrite [-left_distrib, add.right_inv, mul_zero] end theorem neg_mul_eq_neg_mul_symm [simp] : - a * b = - (a * b) := eq.symm !neg_mul_eq_neg_mul theorem mul_neg_eq_neg_mul_symm [simp] : a * - b = - (a * b) := eq.symm !neg_mul_eq_mul_neg theorem neg_mul_neg : -a * -b = a * b := by simp theorem neg_mul_comm : -a * b = a * -b := by simp theorem neg_eq_neg_one_mul : -a = -1 * a := by simp theorem mul_sub_left_distrib : a * (b - c) = a * b - a * c := calc a * (b - c) = a * b + a * -c : left_distrib ... = a * b - a * c : by simp theorem mul_sub_right_distrib : (a - b) * c = a * c - b * c := calc (a - b) * c = a * c + -b * c : right_distrib ... = a * c - b * c : by simp -- TODO: can calc mode be improved to make this easier? -- TODO: there is also the other direction. It will be easier when we -- have the simplifier. theorem mul_add_eq_mul_add_iff_sub_mul_add_eq : a * e + c = b * e + d ↔ (a - b) * e + c = d := calc a * e + c = b * e + d ↔ a * e + c = d + b * e : by rewrite {b*e+_}add.comm ... ↔ a * e + c - b * e = d : iff.symm !sub_eq_iff_eq_add ... ↔ a * e - b * e + c = d : by rewrite sub_add_eq_add_sub ... ↔ (a - b) * e + c = d : by rewrite mul_sub_right_distrib theorem mul_add_eq_mul_add_of_sub_mul_add_eq : (a - b) * e + c = d → a * e + c = b * e + d := iff.mpr !mul_add_eq_mul_add_iff_sub_mul_add_eq theorem sub_mul_add_eq_of_mul_add_eq_mul_add : a * e + c = b * e + d → (a - b) * e + c = d := iff.mp !mul_add_eq_mul_add_iff_sub_mul_add_eq theorem mul_neg_one_eq_neg : a * (-1) = -a := have a + a * -1 = 0, from calc a + a * -1 = a * 1 + a * -1 : by simp ... = a * (1 + -1) : left_distrib ... = 0 : by simp, symm (neg_eq_of_add_eq_zero this) theorem ne_zero_and_ne_zero_of_mul_ne_zero {a b : A} (H : a * b ≠ 0) : a ≠ 0 ∧ b ≠ 0 := have a ≠ 0, from (suppose a = 0, have a * b = 0, by rewrite [this, zero_mul], absurd this H), have b ≠ 0, from (suppose b = 0, have a * b = 0, by rewrite [this, mul_zero], absurd this H), and.intro `a ≠ 0` `b ≠ 0` end structure comm_ring [class] (A : Type) extends ring A, comm_semigroup A definition comm_ring.to_comm_semiring [trans_instance] [s : comm_ring A] : comm_semiring A := ⦃ comm_semiring, s, mul_zero := mul_zero, zero_mul := zero_mul ⦄ section variables [s : comm_ring A] (a b c d e : A) include s local attribute left_distrib right_distrib [simp] theorem mul_self_sub_mul_self_eq : a * a - b * b = (a + b) * (a - b) := by simp theorem mul_self_sub_one_eq : a * a - 1 = (a + 1) * (a - 1) := by simp theorem add_mul_self_eq : (a + b) * (a + b) = a*a + 2*a*b + b*b := calc (a + b)*(a + b) = a*a + (1+1)*a*b + b*b : by simp ... = a*a + 2*a*b + b*b : by rewrite one_add_one_eq_two theorem dvd_neg_iff_dvd : (a ∣ -b) ↔ (a ∣ b) := iff.intro (suppose a ∣ -b, dvd.elim this (take c, suppose -b = a * c, dvd.intro (show a * -c = b, by rewrite [-neg_mul_eq_mul_neg, -this, neg_neg]))) (suppose a ∣ b, dvd.elim this (take c, suppose b = a * c, dvd.intro (show a * -c = -b, by rewrite [-neg_mul_eq_mul_neg, -this]))) theorem dvd_neg_of_dvd : (a ∣ b) → (a ∣ -b) := iff.mpr !dvd_neg_iff_dvd theorem dvd_of_dvd_neg : (a ∣ -b) → (a ∣ b) := iff.mp !dvd_neg_iff_dvd theorem neg_dvd_iff_dvd : (-a ∣ b) ↔ (a ∣ b) := iff.intro (suppose -a ∣ b, dvd.elim this (take c, suppose b = -a * c, dvd.intro (show a * -c = b, by rewrite [-neg_mul_comm, this]))) (suppose a ∣ b, dvd.elim this (take c, suppose b = a * c, dvd.intro (show -a * -c = b, by rewrite [neg_mul_neg, this]))) theorem neg_dvd_of_dvd : (a ∣ b) → (-a ∣ b) := iff.mpr !neg_dvd_iff_dvd theorem dvd_of_neg_dvd : (-a ∣ b) → (a ∣ b) := iff.mp !neg_dvd_iff_dvd theorem dvd_sub (H₁ : (a ∣ b)) (H₂ : (a ∣ c)) : (a ∣ b - c) := dvd_add H₁ (!dvd_neg_of_dvd H₂) end /- integral domains -/ structure no_zero_divisors [class] (A : Type) extends has_mul A, has_zero A := (eq_zero_or_eq_zero_of_mul_eq_zero : ∀a b, mul a b = zero → a = zero ∨ b = zero) theorem eq_zero_or_eq_zero_of_mul_eq_zero {A : Type} [no_zero_divisors A] {a b : A} (H : a * b = 0) : a = 0 ∨ b = 0 := !no_zero_divisors.eq_zero_or_eq_zero_of_mul_eq_zero H theorem eq_zero_of_mul_self_eq_zero {A : Type} [no_zero_divisors A] {a : A} (H : a * a = 0) : a = 0 := or.elim (eq_zero_or_eq_zero_of_mul_eq_zero H) (assume H', H') (assume H', H') structure integral_domain [class] (A : Type) extends comm_ring A, no_zero_divisors A, zero_ne_one_class A section variables [s : integral_domain A] (a b c d e : A) include s theorem mul_ne_zero {a b : A} (H1 : a ≠ 0) (H2 : b ≠ 0) : a * b ≠ 0 := suppose a * b = 0, or.elim (eq_zero_or_eq_zero_of_mul_eq_zero this) (assume H3, H1 H3) (assume H4, H2 H4) theorem eq_of_mul_eq_mul_right {a b c : A} (Ha : a ≠ 0) (H : b * a = c * a) : b = c := have b * a - c * a = 0, from iff.mp !eq_iff_sub_eq_zero H, have (b - c) * a = 0, by rewrite [mul_sub_right_distrib, this], have b - c = 0, from or_resolve_left (eq_zero_or_eq_zero_of_mul_eq_zero this) Ha, iff.elim_right !eq_iff_sub_eq_zero this theorem eq_of_mul_eq_mul_left {a b c : A} (Ha : a ≠ 0) (H : a * b = a * c) : b = c := have a * b - a * c = 0, from iff.mp !eq_iff_sub_eq_zero H, have a * (b - c) = 0, by rewrite [mul_sub_left_distrib, this], have b - c = 0, from or_resolve_right (eq_zero_or_eq_zero_of_mul_eq_zero this) Ha, iff.elim_right !eq_iff_sub_eq_zero this -- TODO: do we want the iff versions? theorem eq_zero_of_mul_eq_self_right {a b : A} (H₁ : b ≠ 1) (H₂ : a * b = a) : a = 0 := have b - 1 ≠ 0, from suppose b - 1 = 0, H₁ (!zero_add ▸ eq_add_of_sub_eq this), have a * b - a = 0, by simp, have a * (b - 1) = 0, by rewrite [mul_sub_left_distrib, mul_one]; apply this, show a = 0, from or_resolve_left (eq_zero_or_eq_zero_of_mul_eq_zero this) `b - 1 ≠ 0` theorem eq_zero_of_mul_eq_self_left {a b : A} (H₁ : b ≠ 1) (H₂ : b * a = a) : a = 0 := eq_zero_of_mul_eq_self_right H₁ (!mul.comm ▸ H₂) theorem mul_self_eq_mul_self_iff (a b : A) : a * a = b * b ↔ a = b ∨ a = -b := iff.intro (suppose a * a = b * b, have (a - b) * (a + b) = 0, by rewrite [mul.comm, -mul_self_sub_mul_self_eq, this, sub_self], have a - b = 0 ∨ a + b = 0, from !eq_zero_or_eq_zero_of_mul_eq_zero this, or.elim this (suppose a - b = 0, or.inl (eq_of_sub_eq_zero this)) (suppose a + b = 0, or.inr (eq_neg_of_add_eq_zero this))) (suppose a = b ∨ a = -b, or.elim this (suppose a = b, by rewrite this) (suppose a = -b, by rewrite [this, neg_mul_neg])) theorem mul_self_eq_one_iff (a : A) : a * a = 1 ↔ a = 1 ∨ a = -1 := have a * a = 1 * 1 ↔ a = 1 ∨ a = -1, from mul_self_eq_mul_self_iff a 1, by rewrite mul_one at this; exact this -- TODO: c - b * c → c = 0 ∨ b = 1 and variants theorem dvd_of_mul_dvd_mul_left {a b c : A} (Ha : a ≠ 0) (Hdvd : (a * b ∣ a * c)) : (b ∣ c) := dvd.elim Hdvd (take d, suppose a * c = a * b * d, have b * d = c, from eq_of_mul_eq_mul_left Ha (mul.assoc a b d ▸ this⁻¹), dvd.intro this) theorem dvd_of_mul_dvd_mul_right {a b c : A} (Ha : a ≠ 0) (Hdvd : (b * a ∣ c * a)) : (b ∣ c) := dvd.elim Hdvd (take d, suppose c * a = b * a * d, have b * d * a = c * a, from by rewrite [mul.right_comm, -this], have b * d = c, from eq_of_mul_eq_mul_right Ha this, dvd.intro this) end namespace norm_num local attribute bit0 bit1 add1 [reducible] local attribute right_distrib left_distrib [simp] theorem mul_zero [mul_zero_class A] (a : A) : a * zero = zero := by simp theorem zero_mul [mul_zero_class A] (a : A) : zero * a = zero := by simp theorem mul_one [monoid A] (a : A) : a * one = a := by simp theorem mul_bit0 [distrib A] (a b : A) : a * (bit0 b) = bit0 (a * b) := by simp theorem mul_bit0_helper [distrib A] (a b t : A) (H : a * b = t) : a * (bit0 b) = bit0 t := by rewrite -H; simp theorem mul_bit1 [semiring A] (a b : A) : a * (bit1 b) = bit0 (a * b) + a := by simp theorem mul_bit1_helper [semiring A] (a b s t : A) (Hs : a * b = s) (Ht : bit0 s + a = t) : a * (bit1 b) = t := by simp theorem subst_into_prod [has_mul A] (l r tl tr t : A) (prl : l = tl) (prr : r = tr) (prt : tl * tr = t) : l * r = t := by simp theorem mk_cong (op : A → A) (a b : A) (H : a = b) : op a = op b := by simp theorem neg_add_neg_eq_of_add_add_eq_zero [add_comm_group A] (a b c : A) (H : c + a + b = 0) : -a + -b = c := begin apply add_neg_eq_of_eq_add, apply neg_eq_of_add_eq_zero, simp end theorem neg_add_neg_helper [add_comm_group A] (a b c : A) (H : a + b = c) : -a + -b = -c := begin apply iff.mp !neg_eq_neg_iff_eq, simp end theorem neg_add_pos_eq_of_eq_add [add_comm_group A] (a b c : A) (H : b = c + a) : -a + b = c := begin apply neg_add_eq_of_eq_add, simp end theorem neg_add_pos_helper1 [add_comm_group A] (a b c : A) (H : b + c = a) : -a + b = -c := begin apply neg_add_eq_of_eq_add, apply eq_add_neg_of_add_eq H end theorem neg_add_pos_helper2 [add_comm_group A] (a b c : A) (H : a + c = b) : -a + b = c := begin apply neg_add_eq_of_eq_add, rewrite H end theorem pos_add_neg_helper [add_comm_group A] (a b c : A) (H : b + a = c) : a + b = c := by simp theorem sub_eq_add_neg_helper [add_comm_group A] (t₁ t₂ e w₁ w₂: A) (H₁ : t₁ = w₁) (H₂ : t₂ = w₂) (H : w₁ + -w₂ = e) : t₁ - t₂ = e := by simp theorem pos_add_pos_helper [add_comm_group A] (a b c h₁ h₂ : A) (H₁ : a = h₁) (H₂ : b = h₂) (H : h₁ + h₂ = c) : a + b = c := by simp theorem subst_into_subtr [add_group A] (l r t : A) (prt : l + -r = t) : l - r = t := by simp theorem neg_neg_helper [add_group A] (a b : A) (H : a = -b) : -a = b := by simp theorem neg_mul_neg_helper [ring A] (a b c : A) (H : a * b = c) : (-a) * (-b) = c := by simp theorem neg_mul_pos_helper [ring A] (a b c : A) (H : a * b = c) : (-a) * b = -c := by simp theorem pos_mul_neg_helper [ring A] (a b c : A) (H : a * b = c) : a * (-b) = -c := by simp end norm_num attribute [simp] zero_mul mul_zero at simplifier.unit attribute [simp] neg_mul_eq_neg_mul_symm mul_neg_eq_neg_mul_symm at simplifier.neg attribute [simp] left_distrib right_distrib at simplifier.distrib